Digital storytelling: engaging young people to communicate for digital media literacy - Ambigapathy Pandian,; Shanthi Balraj Baboo,; Lim, Jing Yi (Penerbit Universiti Kebangsaan Malaysia, 2020)
Digital stories are powerful forces in the lives of young people as they shape opinions, assumptions, and biases about the knowledge of everyday lives. This paper presents the findings of an exploratory project that saw secondary school students participating in a digital storytelling project. Underpinning this project was an interest in cultivating digital media literacy among young people. Data analysed included a self-assessment questionnaire, focus group discussions with young people and the production of short 1-3 minute digital stories on various issues related to online cultures. The first part of the article looks at the digital competences of young people. The findings of a self-assessment revealed that the respondents felt generally capable when working with information, and moderately capable of communication and safety but had difficulty with content creation and problem-solving skills.The findings of the second part of the study revealed that young people get much enjoyment and feel smart and knowledgeable as they scroll quickly through an online search on information, images, news, and stories. They are content consumers and content creators who enjoy dramatic engagements and can produce stories as communication texts. However, it was also found that the students confronted difficulties in evaluating the relevance and usefulness of information as well as in expressing their ideas through different modes of visual communication. By way of conclusion, this paper calls for the creation of a state-based advisory committee composed of educators, researchers and media practitioners who will work towards building digital media literacy.